2012
DOI: 10.1121/1.3672684
|View full text |Cite
|
Sign up to set email alerts
|

Use of an adaptive-bandwidth protocol to measure importance functions for simulated cochlear implant frequency channels

Abstract: The Articulation Index and Speech Intelligibility Index predict intelligibility scores from measurements of speech and hearing parameters. One component in the prediction is the frequencyimportance function, a weighting function that characterizes contributions of particular spectral regions of speech to speech intelligibility. The purpose of this study was to determine whether such importance functions could similarly characterize contributions of electrode channels in cochlear implant systems. Thirty-eight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 55 publications
0
15
1
Order By: Relevance
“…The present study also extends the previous approach of Whitmal and DeRoy (2012) for use in applications involving low-fidelity speech. The Whitmal/DeRoy protocol measured recognition scores for highly intelligible speech at five fixed performance levels between 15.9%-and 84.1%-correct.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…The present study also extends the previous approach of Whitmal and DeRoy (2012) for use in applications involving low-fidelity speech. The Whitmal/DeRoy protocol measured recognition scores for highly intelligible speech at five fixed performance levels between 15.9%-and 84.1%-correct.…”
Section: Introductionmentioning
confidence: 76%
“…The signal processing methods utilized in this experiment were used in previous studies and consist of (optional) tone vocoding and adaptive-bandwidth filtering as prescribed by Whitmal and DeRoy (2012). These processes are described below.…”
Section: Signal Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the SII model, third octave bands with 23 center frequencies between 160 and 8000 Hz all contribute to speech intelligibility, 24 suggesting that an optimal frequency map will include these frequencies, although the 25 most important third octave bands are those with center frequencies of 1.6, 2 and 2.5 1 kHz. A study with normal-hearing participants listening to cochlear implant 2 simulations found that the peak in the relative band importance function was 3 approximately half an octave lower for cochlear implant simulations than for 4 unprocessed speech (Whitmal and DeRoy, 2012). This suggests that for CI users, 5 lower frequency sounds are relatively more important for speech intelligibility than 6 higher frequency sounds, when compared to normal-hearing listeners.…”
mentioning
confidence: 98%